SPECIES COMPOSITION OF ICE ALGAL ASSEMBLAGES IN SAROMA KO LAGOON AND RESOLUTE PASSAGE, 1992 (EXTENDED ABSTRACT) (16th Symposium on Polar Biology) - キクチ-カワノベ, キョウコ; クドウ, サカエ; KIKUCHI-KAWANOBE, Kyoko; KUDOH, Sakae (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper